The Hubungan Kebugaran dengan Prestasi Akademik Masa Pandemi Covid-19 - Sajodin Sajodin (Faletehan Health Journal, 2022)
Fitness is an essential component for students to carry out lecture activities. Online lectures during the Covid-19 pandemic for a long period result in boredom, and lack of concentration during learning, causing a decrease in physical activity it can affect fitness which can affect their academic achievement. The purpose of this study was to analyze the relationship between fitness and achievement. This research uses a correlational description method with a cross-sectional design. The population in this study was 155 students, and the number of samples used by the Slovin formula so that the sample was 61 students. The results of this study indicate that the fitness level is in the perfect category, while academic achievement is in a good category. The results of the Spearman Rank test obtained a p-value of 0.341> 0.05, it can be concluded that there is no significant relationship between fitness and academic achievement.